(3eMGSHI GdfaWs - (3NGdO Cejf(B, (3YHO Gddgs ((3YeGf(B:s (3OGQ hGFd ddfTQ(B,s, 2001)
(3NUGFU eMGSHI GdfaW, GdOdjd GdeMGSHj aj TQcGJ GfJGL GdfaW, eUQhaGJ GdESJcTGa hGdMUhd Ydi GdYbhO GdEeJjGR, GdCdGJ h GdeYOGJ, GdEgdGc aj TQcGJ GfJGL GdfaW , WHjYI GdCUhd GdeJfGbUI hNUGFUgG, faGP GdeeJdcGJ GdefJLI, GdYbhO ZjQ GdeWhQI, eUGQHa GdMaQ hEYOGO HFQ GdEfJGL, JcdaI eQGMd GdEfJGL, GdJcGdja GdeTJQcI aj UfGYI GdfaW, JUhjQ fJjLI GdfTGW hHjGf GdeQcR GdeGdjs
Keywords: (3GdHJQhds; (3eMGSHI(B- (3GdTQcGJs